(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
The aim of the research is to test the impact of the stability of private Syrian Islamic banks listed on the Damascus Securities Exchange on the quality of their accounting profits during the period (2011-2022) with a sample consisting of three private Syrian Islamic banks (Syria International Islamic Bank, Cham Bank and Al Baraka Bank Syria), where banking stability was measured. Which represents the stable variable in the Bank-O-Mater index, which consists of several financial ratios. The financial leverage ratio was also added to measure creditworthiness as an independent variable supporting the (S) indicator. The quality of accounting profits, which represented the dependent variable, was measured with the income smoothing index, which is inversely proportional to quality. The descriptive analytical approach was followed for the theoretical side and some previous studies, and the comparative analytical approach for the applied side of the study while listing the values ​​of the indicators, and the descriptive and standard statistical approach in testing the research objective according to panel models using the Eviews(10) statistical program. The research concluded that the Syrian Islamic banks had banking stability and the quality of their accounting profits despite the crises that the country went through, but they did not have creditworthiness. The research also concluded that the stability of the Syrian Islamic banks and their creditworthiness have a positive impact on the quality of their accounting profits, that is, the more banking stability increases The value of the income smoothing index decreased and the quality of accounting profits increased. One of the research’s recommendations was that it is necessary for Syrian Islamic banks to direct their surplus liquidity towards optimal investments and raise the values ​​and levels of direct credit facilities provided to customers, which contributes to moving the wheel of the economy and benefiting from the profits earned again, which reduces the burden on managers in searching for ways to achieve profits.